Plant regeneration as affected by plant growth regulators (PGR) in mangosteen (Garcinia mangostana L.) - Sirchi, Mohammad Hossein Torabi; Abdul Kadir, Mihdzar; Abdul Aziz, Maheran; Abdul Rashid, Azmi; Rafat, Arash; Javadi, Mohammad Bagher (Academic Journals, 2008)
A protocol was developed for in vitro plantlet regeneration of mangosteen (Garcinia Mangostana L.) from shoot tip, stem and seed explants. Shoot tip explants produced the highest mean number of shoots per explant on media supplemented with 1.0 mg/L 6-benzylaminopurin (BAP) and 0.05 mg/L kinetin (KIN) (73.3). On medium containing 0.1 mg/L BAP and 0.05 mg/L KIN, the highest mean shoot height reached 1.2 cm. The highest percentage of callus formed (90%) was obtained in treatment containing 0.20 mg/L KIN. The effect of BAP in combination with α-naphthalene acetic acid (NAA) was also studied. On half seed explants, the combination of 4 mg/L (w/v) of BAP with 0.2 mg/L (w/v) of (NAA) produced the highest number of shoots per explant (75). In medium containing 2 mg/L (w/v) of BAP and 0.2 mg/L (w/v) of NAA, the mean shoot height reached 1.79 cm also The highest percentage of callus formation (90%) was obtained on treatment containing 0.5 mg/L (w/v) of NAA. For rooting, pretreatment in different indol-3-butyric acid (IBA) and NAA concentrations and comparison of MS salt strengths were evaluated. Identical pattern occurred on medium containing one-quarter strength MS salt and the highest mean number of roots per explant (1.17) was produced in treatment with 2 mg/L IBA. The highest percentage of root formation was obtained on one-quarter strength MS salt medium containing 0.1 mg/L NAA (90.4%). Rooted plantlets were acclimatized on medium composed of soil + sand + organic matters + vermiculite according to the ratio (2: 2: 1: 1).